PENGEMBANGAN EKONOMI BIRU BERBASIS HASIL LAUT DI PULAU MARINGKIK MELALUI EDUKASI DAN PENDAMPINGAN PENGOLAHAN IKAN TANGKAPAN NELAYAN - Waspodo, Saptono; Fahlevi, Muhammad Fahad; Ningrum, Bq Aulia Anita; Qur’aini , Rena Tilla; Mawardiah, Ainun Mawardiah; Wardia, Wardia; Huda, Nurul Huda; Zulhijjah, Indah Zulhijjah; Ningrum, Aditya Ningrum; Rachmadhan, Ilham Rachmadhan; Rifqi, M. Syarief Murtadho Rifqi (Jurnal Wicara, 2024)
Maringkik Island has significant fishing potential that has not yet been fully utilized. This article discusses a community service program aimed at improving marine resource management through education and guidance. The program includes training in fish processing and packaging techniques, implementation of these techniques, and optimization of waste management. Results show an improvement in product quality, a reduction in environmental impact, and the empowerment of the local community.